Savings and Loan Cooperative of Tridana Mandiri in Denpasar - Desak Gde Dwi Arini; Putu Ayu Sriasih Wesna; Ni Made Sukaryati Karma; Desak Ade Devicia Cempaka; Ida Ayu Gede Wulandari (Fakultas Hukum, Universitas Warmadewa, 2022)
As a higher education institution, Warmadewa University must ensure that it always adheres to the Tridharma of Higher Education in accordance with the predetermined vision and mission. Now every lecturer is encouraged to be able to package community service activities both in groups and individually which will later show concern for the community. Community service activities can be carried out by providing enlightenment by providing legal counseling and consultation to the community in various fields of life in the economic field. One thing that should be observed is the existence of a credit agreement, where it is expected that every cooperative business entity is required to have an agreement in this case a credit agreement. Civil Code. Other matters will be contained in an agreement that is easier to change according to economic developments. In the end, this program is expected to be able to provide understanding and solutions to cooperative business entities, especially the Tridana Mandiri Denpasar Savings and Loans Cooperative, to be able to continue to exist as part of a business entity that is developing its existence. When a customer does not pay an obligation, which is called a default, the dispute resolution process is attempted by way of deliberation or kinship.